Pengaruh Latihan Imagery Terhadap Peningkatan Kemampuan Free Throw Ekstrakurikuler SMP Negeri 1 Watampone - Arfah, Arif Ardian; Badaru, Benny; Sahabuddin, Sahabuddin; Suyudi, Imam; Hudain, Muh. Adnan (Prodi Pendidikan Jasmani dan Olahraga, 2025)
This study is an experimental research that aims to find out whether there is an effect of the application of imagery on improving the ability to shoot free throw This study uses two groups of pre-test post-test control design using a total of 20 athletes. The results showed that imagery exercises had a significant effect on improving free throw shooting ability , with the male experimental group's imagery exercises showing a higher average improvement (μA1 81.20 > μA2 13.20) with a score difference of 5.00 so that it has a more significant influence compared to the men's control group exercise on the improvement of free throw ability. The imagery exercises of the women's experimental group showed a higher average increase (μA1 19.40 > 11.20 μA2) with a difference of value of 2.20 so that it had a more significant effect compared to the women's control group exercises on the improvement of free throw ability. Based on these data, it can be concluded that the application of imagery exercises has a significant influence on improving free throw ability.